Dawan Language in Public Space (A Linguistic Landscape Study in Kota Kupang and Soe) - N. Benu, Naniana (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
Dawan language as well known by its speakers as Uab Meto is an Austronesian language spoken in west Timor by Atoin Meto. Various world changes and developments nowadays have also caused a change in the culture of Atoin Meto as well as their language. This article is aimed at investigating the existence of Dawan language in public spaces of Kota Kupang and Soe city. Data was obtained through observation and documentation using digital camera for taking pictures of the written sign of Dawan language in public spaces in the two cities. Interview also applied to know the native speakers’ perception. The result shows that there are 29 signs found in all around these two cities. Relating to the perceptions, the native speaker seemed to confuse and hesitated to state their position on the importance of Dawan language in the public space.